REVEALING OF DEFECTS OF BEARINGS WITH THE HELP OF MODERN METHODS OF CONTROL OF TECHNOLOGICAL EQUIPMENT OF HARDWARE PRODUCTION - S. M. Piskun; V. E. Guber (Литьë и металлургия)
It is shown that using of modern methods and means of technical diagnostics will allow to provide reliable accident-free exploitation of equipment, to decrease considerably labour-intensiveness, period of repair and accordingly production expenses.